Are there differences in auscultatory pulse in total blood flow restriction between positions, limbs and body segments? - Rodrigues Neto, Gabriel (2018)
Verification of the auscultatory pulse in total blood flow restriction (BFR) has been a limiting factor in studies due to the way in which it is evaluated and prescribed, as hemodynamic measurements can be directly affected by gravity. The aim of the present study was to compare the auscultatory pulse in BFR between positions, genders, limbs and body segments in healthy young individuals. A total of 156 subjects participated in the study, 76 of whom were male and 80 of whom were female (23.9±3.7 years, 66.5±11.5 kg, 1.67±0.07 m). After filling in registration data, anthropometry was evaluated, and BFR pressure was determined. BFR was evaluated in a randomized manner in both limbs (upper and lower) and in both segments (right and left) in the following positions: a) lying in the supine position; B) sitting with knees and trunk at 90°; and c) standing in the anatomical position. Significant differences were observed between the lying, sitting and standing positions (p<0.05), between genders (p<0.05), between limbs (p<0.05) and between the right and left segments in the lower limb in both genders [males (p=0.014) and females (p=0.009)] in the lying position. However, no significant differences were observed between the right and left segments in the upper limbs (p>0.05). The BFR point appears to differ between positions, genders, lower limbs and segments. Therefore, it is recommended that health professionals should check the BFR point in the position relating to the exercise that will be performed, taking into account gender, lower limbs and body segments.